Numerical modeling of explosion of a reinforced concrete magazine : effect of steel reinforcements - Wang, Wen Feng. (2010)
This is a report for the Final Year Project on the topic of numerical modeling of explosion of a reinforced concrete magazine – effect of steel reinforcements. The report starts with the literature review on the past researches on numerical modeling of reinforced concrete magazine. After the analysis of simulation methodology, the report presents the numerical simulation results and some found outs on the strengthening effect of steel reinforcements. Steel bar connection type and reinforcement ratio are the two main areas under investigation. Simulation cases of different connection types or different reinforcement ratios are carried out under different blast loading densities, from low loading density to high loading density. The results are compared and discussed in the following aspects: deformation and fracture patterns, pressure and impulse, and debris velocity. Conclusions are drawn and future studied directions are recommended at the end of the report.